Development and validation of an online academic resilience scale for college students - Zheng, Weidong; Ratanaolarn, Thanin; Sriwisathiyakun, Kanyarat; Jiang, Genghao (Edelweiss Applied Science and Technology, 2025)
Given the increasing prevalence of online learning, understanding the online academic resilience of college students is essential for learning analytics and intervention. This study employed mixed methods to develop and validate a new instrument, the Online Academic Resilience Scale (OARS). By interviewing 12 college students who had experienced significant online learning challenges and adapted well, 77 items were compiled. Using the Delphi method, 16 items were retained, encompassing four factors: goal focus, learning motivation and efficacy, positive cognition, and course quality. A questionnaire survey was conducted among 317 college students from different cities in China to evaluate the scale’s effectiveness. Results indicated that the scale demonstrated good item discrimination, reliability, and validity. Furthermore, confirmatory factor analysis supported the structural validity of the scale, with chi-square (c2) = 293, degrees of freedom (df) = 98, c2/df = 2.98 < 3, root mean square error of approximation (RMSEA) = 0.079 < 0.08, comparative fit index (CFI) = 0.929 > 0.9, Tucker-Lewis index (TLI) = 0.913 > 0.9, and P-value = 0.0000 < 0.005. The scale is suitable for measuring college students’ online academic resilience and provides a theoretical reference and tool support for related research.